PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING PADA POKOK BAHASAN MAKROMOLEKUL - Wati, Desri; Haryati, Sri; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to develop the student’s activity paper on the subject of macromolecule. The type of this research was reseach and development (R & D) with the 4-D development model which include Define, Design, Develop, and Disseminate. This research was to develop phase and be continue with a definite tryout. This research was conducted in FKIP Riau University. The object of this research was the students’ activity paper based on the discovery learning. The data analysis technique used for this research was descriptive statistic descriptive. The descriptive analysis done by calculated the percentage of validation value. The average score of valuation to four expediency aspect of student’s activity sheet by validator’s team, such as the content properness, the language properness, course and the graphical has expediency value continued is 89,10%,, 90,00%, 10,00%, and 91,67%. Thus, the average score totality of student’s activity paper based on the discovery learning subject of macromolecule is 92,69% which is in valid criteria, means that the LKPD Developed is proper to be use. Whereas percentage response of student or collegian is 93,50% to LKPD with very good criteria.Key Words: Student Activity Sheet, Discovery Learning, and Macromolecule.